Analisis Penentuan Harga Jual Pada Industri Consumer: Tinjauan Systematic Literature Review - Aryanti Mega Cahyani; Asti Astuti; Aulia Hakimah; Chaerunnisa A.R; Syifa R (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Determining the selling price is a strategic decision that significantly determines the sustainability and competitiveness of a company, especially in 2025, which is characterized by high business competition, fluctuating production costs, and changes in consumer preferences. This study aims to analyze the concept and strategy of determining selling prices through a Systematic Literature Review (SLR) approach with a focus on the application of target costing as a basis for cost control and pricing. The research method used is qualitative research by reviewing scientific articles from 2023–2025 that are relevant to the topics of selling price determination, cost management, and target costing. The results of the study indicate that target costing is effective as a market-based selling price determination approach because it is able to integrate market prices, profit targets, and production cost efficiency. In addition, the effectiveness of selling price determination increases when target costing is combined with the Activity-Based Costing method and value engineering. The conclusion of this study confirms that determining selling prices in 2025 requires a strategic, adaptive, and market-oriented approach to maintain company profitability and sustainability